Aplicación digital como recurso de apoyo para la promoción y prevención en salud oral del niño escolar 6 a 11 años (2023)
The development of Information and Communication Technologies and their easy access make this an educational alternative that contributes to increasing the quality of education, facilitating the teaching-learning process with virtual media, this allows us to accompany the interventions and promotional activities in oral health.